Εγγραφή μικρο-δομών χρησιμοποιώντας λέιζερ φεμτοδευτερολέπτου - Ττοφή, Ειρήνη; Μωυσέως, Αντρέας; Ποσπορή, Αντρέας (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
This study explores the inscription of micro-structures using a femtosecond laser. The structures were inscribed in two different materials (silicon and silica) and the selection of these materials was related to their specific properties. These structures are micro-scale, and can subsequently be used in applications in micro-optical circuits and micro-fluidic systems. Specifically, the structures constructed are a micro fluidic device, which can be used to precisely control the handling of fluids on a very small scale. Furthermore, we inscribed phase masks within the bulk volume of silica; these are typically used for recording Bragg gratings and can be used as optical sensors. The inscription of these structures was achieved using a High-Q FemtoREGEN femtosecond laser (4-class), with the high intensity pulses interacting with the material fundamentally modifying its physical and optical properties at the point where the laser beam is focused. The structures we designed using an algorithm (G-Code), which determined the speed and sample motion relative to the inscribing laser beam. In general, the intensity of the laser and the translation speed determines the depth and width of the structures. After the creation of micro-structures we measured their dimensions. For these measurements we used equipment of the latest technology, such as an optical profilometer, an atomic force microscope and an optical microscope, where each piece of equipment showed the structures on a different length scale. Subsequently, conclusions were reached about the dimensions and characteristics of these structures. Following several experimental trials, we recorded uniform structures with constant width and depth, in the volume and on the surface of the material. Specifically, in these tests, various algorithms are applied, representing defined structures in combination with the change of the laser focal point. Finally, we confirmed that G-code offers the ability to create complex structures, where the user can give specific parameters and commands to create them. This allows for a broad application of each structure separately in various fields of technology.
Keywords: Laser; Inscription Micro-Structures; Femtosecond Laser; Λάζερ; Κατασκευή Μικρο-Δομών; Λέιζερ Φεμτοδευτερεολέπτου